Workforce diversity : a human resource development perspective towards organizational performance - Ismail, Maimunah; Arokiasamy, Lawrence (EuroJournals, 2008)
Workforce diversity has become an important issue in Malaysia as it is essentially linked to organizational performance. This implies that organizations should be more competitive in today’s globalisation. Thus workforce diversity is one of the fundamental solutions to enter the international arena. Specifically, organisations must invest necessary resources on workforce diversity in order to create opportunities for organisational performance. This article examines the extent to which workforce diversity has a direct impact on organizational performance. Finally, this article suggests that organizations should meaningfully redefine the notion of workforce diversity by reconsidering their broader theoretical underpinnings for a better human resource development practice.